Reproductive biology of Vasconcellea quercifolia A. St.-Hil. (Caricaceae), a moth-pollinated ‘highland papaya’ - Cerino, María Carolina (2015)
Vasconcellea species, often referred to as highland papayas, are wild relatives of common papaya (Carica papaya) widely distributed in tropical America, with a preference for cooler climates. The genus deserves special attention as its species show potential as raw materials in the tropical fruit industry, papain source or as genetic resources in breeding programs of C. papaya. However, studies related to breeding system and pollination biology of genus are still unexplored. We characterize the reproductive biology of dioecious Vasconcellea quercifolia, one of the southernmost Caricaceae. According to floral shape and presence of nectar, we expected that this species had a specializated pollination system, with moths as the primary pollinators. To test this, we studied floral biology, floral visitors, pollinators, and breeding system of this species. Controlled pollination experiments show that V. quercifolia is a xenogamous species that depends on its pollinators to set fruits (18 and 79 % fruit and seed set under open-pollination, respectively). Anemophily and apomixis occur very seldom. The treatments of exclusion of floral visitors and pollen load analysis showed that the main pollinators are moths belonging to Arctiidae, Noctuidae, and Pyralidae. The only reward for pollinators is the nectar produced by male flowers. Female flowers are pollinated by deceit because they do not produce floral rewards.